Fatty acid and melatonin-enriched warming: A novel approach using vitrified oocytes and early-stage embryos for patients with poor prognosis - Yoo Ra Ko; Soyoung Kim; Jinkyeong Ha; Seyul Han; Woo Sik Lee; Jin Hee Eum (PLoS ONE, 2026)
Background Cryopreservation and warming can induce cellular stress that impairs oocyte and embryo competence, particularly in poor-prognosis patients. Although fatty acids and melatonin have been proposed to support cytoskeletal stability and reduce oxidative stress, their combined use during warming has not been specifically evaluated. This study evaluated whether co-supplementation with fatty acids and melatonin during warming improves embryological development and clinical outcomes following thawing of vitrified oocytes or early-stage embryos. Methods This retrospective cohort study was conducted at a single fertility centre between August 2022 and December 2024. The embryo-thawed cohort comprised women aged ≥35 years with poor embryo quality, defined as failure to achieve blastocyst cryopreservation in at least two prior in vitro fertilisation cycles. The oocyte-thawed cohort included women aged ≥35 years at vitrification. Warming was performed with or without 1% fatty acids and 10 µM melatonin. Embryological and clinical outcomes were compared using non-parametric analyses, with age-adjusted comparisons by multivariable regression. Results In the oocyte-thawed cohort, warming with fatty acids and melatonin significantly improved oocyte survival (91.4% vs. 76.7%), spindle alignment (71.2% vs. 55.1%), and embryo development, with higher good-quality cleavage (51.0% vs. 24.1%) and blastocyst formation rates (24.6% vs. 10.3%) (all P < 0.001). Clinical pregnancy was also higher in the supplemented group (38.5% vs. 16.1%; adjusted OR 3.21; 95% CI, 1.17–8.82; P = 0.024). In the embryo-thawed cohort, enriched warming increased blastocyst formation (41.4% vs. 29.3%; P = 0.024), high-quality blastocyst rate (51.1% vs. 27.3%; P < 0.001), implantation (26.1% vs. 14.4%; P = 0.002), and clinical pregnancy (51.4% vs. 29.1%; adjusted OR 3.13; 95% CI, 1.75–5.60; P < 0.001). Conclusions Co-supplementation with fatty acids and melatonin during warming improved oocyte survival, spindle alignment, embryo development, and clinical pregnancy outcomes in poor-prognosis patients. This simple, clinically applicable approach may reduce cryo-induced stress and enhance reproductive success.